Respuesta :

C if u need a step-by-step just comment

(-1, -2), (-2, -1) and (2, -4) are solutions to the inequality

The given inequality is:

-x - 2y  >  3

To know which of the points given as options are the solutions to the given inequality, substitute the given points into -x - 2y, anyone that gives a result greater than 3 is a solution to the inequality

For (-1, -2)

Substitute x = -1, and y = -2 into -x - 2y

-(-1) - 2(-2)

= 1 + 4

= 5

Since 5 > 3, (-1, -2) is a solution to the inequality

For (1, -2)

Substitute x = 1, and y = -2 into -x - 2y

-(1) - 2(-2)

= -1 + 4

= 3

Since the result is not greater than 3, (1, -2) is not a solution to the inequality

For (-2, -1)

Substitute x = -2, and y = -1 into -x - 2y

-(-2) - 2(-1)

= 2 + 2

= 4

Since  4 > 3, (-2, -1) is a solution to the inequality

For (2, -4)

Substitute x = 2, and y = -4 into -x - 2y

-(2) - 2(-4)

= -2 + 8

= 6

Since   6 > 3, (2, -4) is a solution to the inequality

Therefore, (-1, -2), (-2, -1), and (2, -4) are solutions to the inequality

Learn more here: https://brainly.com/question/19507846

ACCESS MORE